2010
DOI: 10.15218/zjms.2010.016
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Skin Diseases among Primary School Children

Abstract: Background and objective: Skin diseases constitute serious public health problems throught the world, especially in children. The aim of the study was to determine the preva-lence of skin diseases in primary school children in Erbil city, and its relation to various socio-demographic factors. Methods: A total of 6915 pupils aged 6-15 years were randomly selected from 32 primary schools using multistage random sampling technique. Data regarding general socio-demographic variables were collected from each stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Regarding the body mass index, most of the participants had a normal body mass index (77%), 16.8% were overweight, 4.3% were obese, while only 2% had underweight, as shown in figure 3 In instance, research conducted in Iraq Erbil City found that the frequency of skin illnesses among primary school pupils was 40.6%. [14]. A study conducted in Baghdad in 2010 found that the frequency was 40.9%.…”
Section: Table 31: Sociodemographic Distribution Of the Participantsmentioning
confidence: 98%
See 1 more Smart Citation

Prevalence and Pattern of Skin Disorder among Primaryschool Children in Wasit Governorate, Iraq, 2021

Dr. Basim Abdulrazzaq Abood Algharbawi,
Dr. Sundus Jaafar Mahmood Ai Baraznchi,
Dr. Jawad Kadhim Mahdi Al-Mnehil
2023
Texa. Jour. of Medi. Scie.
“…Regarding the body mass index, most of the participants had a normal body mass index (77%), 16.8% were overweight, 4.3% were obese, while only 2% had underweight, as shown in figure 3 In instance, research conducted in Iraq Erbil City found that the frequency of skin illnesses among primary school pupils was 40.6%. [14]. A study conducted in Baghdad in 2010 found that the frequency was 40.9%.…”
Section: Table 31: Sociodemographic Distribution Of the Participantsmentioning
confidence: 98%
“…Regarding the pattern of the skin disorders, viral infection was the most common, as 20.5% of the participants had skin viral infection, and fungal infection was observed in 12% of the participants, followed by bacterial infection as it observed in 8% of the participants (Table 3.2). In another study that was done in Erbil City, the infectious dermatome was the most prevalent skin disorder; the highest prevalence of these disorders was a parasitic infection, followed by viral infection [14]. While viral infection was the most prevalent cause of skin disorder, a study was done in Turkey, followed by parasitic, fungal, and bacterial [15].…”
Section: Table 31: Sociodemographic Distribution Of the Participantsmentioning
confidence: 99%

Prevalence and Pattern of Skin Disorder among Primaryschool Children in Wasit Governorate, Iraq, 2021

Dr. Basim Abdulrazzaq Abood Algharbawi,
Dr. Sundus Jaafar Mahmood Ai Baraznchi,
Dr. Jawad Kadhim Mahdi Al-Mnehil
2023
Texa. Jour. of Medi. Scie.